The prevalence of Vibrio Cholera Infection among Patients with Diarrheal Infections in flood affected population of Pol-e Dokhtar County: 2019 - Babaei, Zahra; Bahrami, Nikou; khalili, Sahar; pouladi, iman (Archives of Medical Laboratory Sciences, 2020)
Backgrounds: Cholera is an acute diarrheal intestinal infection caused by infection of intestine with vibrio cholera. Cholera is defined as endemic in Iran, thus rapid detection in the early stage of infection is crucial, especially during the disease outbreaks. Materials and Methods: We collected 172 rectal swab samples from patients with diarrheal infections, and sterile beakers were used to collect water samples from some regions of Pol-e Dokhtar city. The collected specimens were transported to the laboratory using Cary-Blair transport medium and were then grown and incubated on alkaline peptone water (APW) and thiosulfate citrate bile salts sucrose (TCBS) agar. Then, all colonies that grew in Kligler Iron Agar (KIA) were cultured. Results: In this study, colonies were grown on APW and TCBS media, and were then transferred to the KIA. None of the colonies were shown to be belonged to V. cholerae strains. Thus, all collected samples were negative for V. cholerae in all patients as well as the drinking water in most regions of the city. Conclusion: The findings of this study suggest that V. cholerae was not the major cause of severe diarrheal infections in a flood-hit population of Pol-e Dokhtar city, and therefore other bacterial and viral agents should be responsible for severe diarrheal illnesses in this population.